2017
DOI: 10.1002/osp4.119
|View full text |Cite
|
Sign up to set email alerts
|

How does plate size affect estimated satiation and intake for individuals in normal-weight and overweight groups?

Abstract: SummaryObjectiveManipulating plate sizes could possibly introduce perceptual biases for judging food satiation and intake, which is thought to be related to the Delbeouf illusion – a visual illusion based on the perceived size of one object related to another. This study was to investigate whether an association exists between an individual's susceptibility to the plate‐size‐effect and their weight status (i.e. normal‐weight versus overweight).MethodsThe study assessed the effect of plate size amongst normal‐w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
1
19
0
2
Order By: Relevance
“…Observations may also be further moderated by BMI, because overweight participants are likely to select smaller portions for social desirability reasons 95 . A more recent study 135 considered the impact of different plate sizes on expected satiation and expected consumption in overweight and lean adults. The authors found that a smaller plate generated higher expected satiation and lower predicted intake, but only in lean participants.…”
Section: Modified Tablewarementioning
confidence: 99%
“…Observations may also be further moderated by BMI, because overweight participants are likely to select smaller portions for social desirability reasons 95 . A more recent study 135 considered the impact of different plate sizes on expected satiation and expected consumption in overweight and lean adults. The authors found that a smaller plate generated higher expected satiation and lower predicted intake, but only in lean participants.…”
Section: Modified Tablewarementioning
confidence: 99%
“…En el caso de participantes del presente estudio con sobrepeso y obesidad, hombres y mujeres no mostraron diferencia en su comportamiento. Esta evidencia supone que las personas con normopeso parecieran tener mayor capacidad de estimación que las personas con sobrepeso y obesidad (Peng, 2017). Ya se ha mencionado que existen diferencias en la estimación calórica en hombres y mujeres (Carels, Konrad y Harper;.…”
Section: Discussionunclassified
“…Otro estudio examinó el efecto de dos tamaños de plato (27 cm y 23 cm) sobre la saciación e ingesta calórica en personas con normopeso y sobrepeso a partir de un cuestionario que contenía fotografías de diez diferentes comidas. Las personas con normopeso reportaron mayor nivel de saciación y menor ingesta que las personas con sobrepeso (Peng, 2017).…”
Section: N F O R M a C I ó N D E L A R T í C U L Ounclassified
See 2 more Smart Citations